Personal adventures in Upper and Lower California, in 1848-9; with the author's experience at the mines. Illustrated by twenty-three drawings ... - Ryan, William Redmond, 1791-1855. (London, W. Shoberl, 1850)
An Englishman, William Redmond Ryan (1791-1855) enlisted in an American regiment bound for California and sailed round the Horn in 1847. Personal adventures in Upper and Lower California (1850), vol. 1, describes that voyage to California as well as military life during the Mexican War in Monterey, La Paz, and San Jose (lower California). The first volume closes with Ryan's description of the peacetime rush to the gold mines and his own journey from Monterey to the San Joaquin Valley to the Stanislaus Mine. Vol. 2, continues his story with a chronicle of daily life at the Stanislaus Mine; his career as a trader; travels through Stockton, Monterey, and Sacramento; life in San Francisco, 1849; the Constitutional Convention; and return voyage via Panama, 1849.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Gold discoveries; California -- Description and travel; Baja California (Mexico : Peninsula) -- Description and travel; Ethnic groups -- California